Cobalt-free LaNi0.4Zn0.1Fe0.5O3-δ as a cathode for solid oxide fuel cells using proton-conducting electrolyte. (8th November 2021) - Wu, Shuai; Liu, Yinhua; Wang, Chao; Dai, Hailu; Wang, Xianfen; Bi, Lei
Abstract: A Zn-doping strategy is employed to tailor the LaNi0.5 Fe0.5 O3-δ material to improve its performance for proton-conducting solid oxide fuel cells (H–SOFCs). Zn can partially replace Ni in the LaNi0.5 Fe0.5 O3-δ lattice to form LaNi0.4 Zn0.1 Fe0.5 O3-δ material. In contrast, ZnO secondary phase can be detected if attempts are made to partially replace Fe with Zn, and the nominal composition LaNi0.5 Fe0.4 Zn0.1 O3-δ cannot be obtained. First-principles calculations indicate that the Zn-doping method lowers the formation energy of oxygen vacancy and decreases the hydration energy, benefiting its application as the cathode for H–SOFCs. As a result, the H–SOFC with the LaNi0.4 Zn0.1 Fe0.5 O3-δ cathode generates a peak power density of 1226 mW cm −2 at 700 °C. In contrast, the peak power density for the cell using the Zn free LaNi0.5 Fe0.5 O3-δ cathode only reaches 722 mW cm −2 at the same testing temperature. The polarization resistance of the cell with the LaNi0.4 Zn0.1 Fe0.5 O3-δ cathode is reduced to 0.043 Ω cm 2 at 700 °C, which is one of the smallest reported for H–SOFCs using cobalt-free cathodes. The high fuel cell performance coupled with the low polarization resistance for the Zn-modified LaNi0.5 Fe0.5 O3-δ suggests that the Zn-doping strategy would be an interesting way to promote the performance of the cobalt-free LaNi0.5 Fe0.5 O3-δ material for H–SOFCs. Highlights: A new LaNi0.4 Zn0.1 Fe0.5 O3-δ material has been prepared. Zn-doping improved the material's properties for H–SOFCs. High cell performance of 1226 mW cm −2 at 700 °C was obtained with the new cathode. First-principles calculations were used to reveal the mechanism.